Does electronic stewardship work?. (21st March 2017) - Lambl, Barbara B; Kaufman, Nathan; Kurowski, Janice; O'Neill, W; Buckley Jr, Frederick; Duram, Maureen; Swartz, Barbara; Phillips, Duncan; Rein, Mitchell; Rubin, Marc
Abstract: Faced with national requirements to promote antimicrobial stewardship and reduce drug-resistant infections, community hospitals are challenged to make the best use of existing resources. Eighteen months after building antibiotic decision support into our electronic order platform, high-risk antibiotic use decreased by 83% ( P  < .001) at our community hospital. Hospital-acquired Clostridium difficile infections declined 24% ( P  = .07).